A review of the prevalence rates of comorbid personality disorders and substance use disorders at the psychotherapy unit at Tara Hospital - Miller, Laura Natasha (My University, 2018)
This study is a retrospective, descriptive study that involved a review of 85 patient files from the Psychotherapy Unit (Ward 4&5) at Tara Hospital, admitted between 01st January to 31st December 2012. The Psychotherapy Unit services patients with personality disorders, together with other comorbid disorders; and provides pharmacological and psychotherapeutic management to such individuals. The study described and analysed demographics, personality traits and disorders, details of substance misuse, taking into account gender and comorbid axis 1 pathology. Options for referral to various substance use treatment facilities were considered, and presence of substance testing was also noted. The majority of patients included in the study were predominantly young, single, unemployed and female. The most common axis II diagnosis was borderline personality disorder. 81% of the individuals included in the study had a comorbid axis 1 psychiatric pathology. Seventy-three percent of the study sample had a substance use disorder, with 33.9% meeting the criteria for substance dependence. There were significant differences observed between types of substances used and frequency, especially with regard to the different personality disorders. Also there was significant gender variability observed between the different personality disorder subtypes. This study highlights the high frequency of comorbidity between individuals with personality disorders and substance use disorders, and other axis 1 pathology in general. It necessitates the need to conduct further research in this group, and consider the possibility of opening a dual diagnosis unit on site, to provide adequate treatment to such a vulnerable subgroup.
Keywords: Substance-Related Disorders; Personality Disorders; Psychotherapy